Envisioning islamic art and architecture
1 online resource (xxx, 311 pages)
Keywords: Envisioning Islamic Art and Architecture: Essays in Honor of Renata Holod is a collection of studies on the portable arts, arts of the book, painting, photography, and architecture spanning the medieval and modern periods and across the historical Islamic lands. The essays reflect the wide-ranging interests and diverse methodologies of Renata Holod and attend to the physical, material, and aesthetic properties of their objects, offer nuanced explanations of complex relations between objects and historical contexts, and remain critically aware of the shape of the field of Islamic art and architecture, its canonical objects, approaches, and historiographies. Essential reading for scholars working on Islam and the Islamic world in the disciplines of history of art and architecture, history, literature, and anthropology. With contributions by María Judith Feliciano, Christiane Gruber, Leslee Katrina Michelsen, Nancy Micklewright, Stephennie Mulder, Johanna Olafsdotter, Yael Rice, Cynthia Robinson, David J. Roxburgh, D. Fairchild Ruggles, Alison Mackenzie Shah, and Pushkar Sohoni.